Rapid, efficient, and simple motor neuron differentiation from human pluripotent stem cells. Issue 1 (December 2015) - Shimojo, Daisuke; Onodera, Kazunari; Doi-Torii, Yukiko; Ishihara, Yasuharu; Hattori, Chinatsu; Miwa, Yukino; Tanaka, Satoshi; Okada, Rina; Ohyama, Manabu; Shoji, Masanobu; Nakanishi, Atsushi; Doyu, Manabu; et al.
Abstract Background Human pluripotent stem cells (hPSCs) are being applied in regenerative medicine and for thein vitro modeling of human intractable disorders. In particular, neural cells derived from disease-specific human induced pluripotent stem cells (hiPSCs) established from patients with neurological disorders have been used asin vitro disease models to recapitulatein vivo pathogenesis because neural cells cannot be usually obtained from patients themselves. Results In this study, we established a rapid, efficient, and simple method for efficiently deriving motor neurons from hPSCs that is useful for pathophysiological analysis and the development of drugs to treat motor neuron diseases. Treatment with GSK3β inhibitors during the initial phase of differentiation in combination with dual SMAD inhibition was sufficient to inducePAX6 + andSOX1 + neural progenitors within 1 week, and subsequent treatment with retinoic acid (RA) and purmorphamine, which activates sonic hedgehog (SHH) signaling, resulted in the highly efficient induction of HB9+ and ISL-1+ motor neurons within 2 weeks. After 4 weeks of monolayer differentiation in motor neuron maturation medium, hPSC-derived motor neurons were shown to mature, displaying larger somas and clearer staining for the mature motor neuron marker choline acetyltransferase (ChAT). Moreover, hPSC-derived motor neurons were able to form neuromuscular junctions with human myotubesin vitro and induced acetylcholine receptor (AChR) clustering, as detected by Alexa 555-conjugated α-Bungarotoxin (α-BTX), suggesting that these hPSC-derived motor neurons formed functional contacts with skeletal muscles. This differentiation system is simple and is reproducible in several hiPSC clones, thereby minimizing clonal variation among hPSC clones. We also established a system for visualizing motor neurons with a lentiviral reporter for HB9 (HB9 e438 ::Venus ). The specificity of this reporter was confirmed through immunocytochemistry and quantitative RT-PCR analysis of high-positive fractions obtained via fluorescence-activated cell sorting (FACS), suggesting its applicability for motor neuron-specific analysis. Conclusions Our motor neuron differentiation system and lentivirus-based reporter system for motor neurons facilitate the analysis of disease-specific hiPSCs for motor neuron diseases.